Identifying Beetle Species Using Machine Learning - Whitten, Samantha (My University, 2019)
Machine learning Artificial Intelligence (AI) hold the potential to benefit farmers and the environment. Computer models can identify lady beetles in images, and, with more training, possibly determine their presence in crop fields. As predators, lady beetles could be a strong indicator of aphid infestations. Using this information and Al technology, farmers could simultaneously reduce costs and environmental damage by having the ability to identify an infested area and focus pesticide applications on a specified section rather than on an entire field,. Before we reach this point, we must determine whether Al or human identification is more reliable and efficient.
Keywords: USDA NIFA 2019-67032-29071